Design, Simulation, and Experimental Validation of Quadrupedal Robotics Platforms - Bianchi, Alessandro; Marchetti, Lorenzo; Simeone, Andrea; Boccia, Elena; D'Amico, Gabriele; Rizzo, and Marco (Journal of Computer Engineering, 2024)
This paper outlines the design process for achieving a novel four-legged robot for exploration and rescue tasks. This application is also intended as an educational mean for masters’ students aiming at gaining skills in designing and operating a complex mechatronic system. The design process starts with an analysis of the desired locomotion and definition of the main requirements and constraints. Then, the paper focuses on the key design challenges, including analytical/numerical modeling and simulations of kinematic and dynamic performances. Specific attention is addressed to the manufacturing of a proof-of-concept prototype, including mechanical and control hardware, as well as the development of the needed software for an autonomous operation. Preliminary tests were carried out, to validate the main features required by the final prototype, to prove its feasibility and user-friendliness, as well as the effectiveness of this complex mechatronic design task for successfully engaging students towards learning complex theoretical, numerical, and practical skills.